Tsc13p Is Required for Fatty Acid Elongation and Localizes to a Novel Structure at the Nuclear-Vacuolar Interface in Saccharomyces cerevisiae - Kohlwein, Sepp D.; Eder, Sandra; Oh, Chan-Seok; Martin, Charles E.; Gable, Ken; Bacikova, Dagmar; Dunn, Teresa (Molecular and cellular biology, 2001)
The TSC13/YDL015c gene was identified in a screen for suppressors of the calcium sensitivity of csg2Δ mutants that are defective in sphingolipid synthesis. The fatty acid moiety of sphingolipids in Saccharomyces cerevisiae is a very long chain fatty acid (VLCFA) that is synthesized by a microsomal enzyme system that lengthens the palmitate produced by cytosolic fatty acid synthase by two carbon units in each cycle of elongation. TheTSC13 gene encodes a protein required for elongation, possibly the enoyl reductase that catalyzes the last step in each cycle of elongation. The tsc13 mutant accumulates high levels of long-chain bases as well as ceramides that harbor fatty acids with chain lengths shorter than 26 carbons. These phenotypes are exacerbated by the deletion of either the ELO2 or ELO3gene, both of which have previously been shown to be required for VLCFA synthesis. Compromising the synthesis of malonyl coenzyme A (malonyl-CoA) by inactivating acetyl-CoA carboxylase in atsc13 mutant is lethal, further supporting a role of Tsc13p in VLCFA synthesis. Tsc13p coimmunoprecipitates with Elo2p and Elo3p, suggesting that the elongating proteins are organized in a complex. Tsc13p localizes to the endoplasmic reticulum and is highly enriched in a novel structure marking nuclear-vacuolar junctions.